(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Financial, human, and social types of capital are widely discussed in the literature as they relate to entrepreneurial success. To date, however, positive psychological capital has not received adequate attention by academics or practitioners. Psychological capital refers to psychological states such as hope, confidence, resilience, and optimism, which are discussed in this paper as being crucial for entrepreneurs to genuinely demonstrate. The four states are discussed and the Expanding Capital Model for Entrepreneurial Success is introduced.